2021
DOI: 10.3390/agriculture12010016
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cover and Land Management Factors for Soil Loss Prediction in Cameron Highlands, Malaysia

Abstract: Many new agricultural activities resulted in severe soil erosion across the Cameron Highlands’ land surface. Therefore, this study determines the cover (C) and land management (P) factors of the USLE for predicting soil loss risk in Cameron Highlands using a Geographic Information System (GIS). For this study, data from the Department of Agriculture Malaysia (DOAM) and the Department of Town and Country Planning Malaysia (PLANMalaysia) were used to generate several C&P factors in the Cameron Highlands. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Based on the land use data, more than 89.9 per cent of the landslide events have occurred on land with agricultural activities (short-term farming and vegetables) and urban development (residential and tourism). According to the [6,7], many agricultural activities without proper irrigation water and extensive land clearing for urban development were one of the major contributors to soil erosion, which consequently weaken surface slope and lead to landslides. Besides, intense rainfall in Cameron Highlands triggered continuous soil loss which increase the chances of landslide occurrence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the land use data, more than 89.9 per cent of the landslide events have occurred on land with agricultural activities (short-term farming and vegetables) and urban development (residential and tourism). According to the [6,7], many agricultural activities without proper irrigation water and extensive land clearing for urban development were one of the major contributors to soil erosion, which consequently weaken surface slope and lead to landslides. Besides, intense rainfall in Cameron Highlands triggered continuous soil loss which increase the chances of landslide occurrence.…”
Section: Resultsmentioning
confidence: 99%
“…Inadequate control and regulation of development, particularly in the agricultural sector in highland regions, have been identified as significant factors that contribute to a high incidence of landslides in Cameron Highlands [5][6][7]12]. In recent times, a total of 12 landslide occurrences have been reported in the region of Cameron Highlands [13] which transpired for two (2) hours duration characterised by heavy precipitation.…”
Section: Landslide In Cameron Highlandsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, USLE is utilised to determine the A-factor, which necessitates acquiring R, K, LS, C, and P, in order to compute soil loss/erosion. All components' values were included in equation (1) using information from the data published by the Department of Agriculture and PLANMalaysia, to be established by REDAC USM (Mahamud et al, 2022). The developed soil loss risk map is shown in Figure 5 while Table 2 shows the area of soil loss established in the study concerning the soil loss class category.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that erosivity in humid tropics is very high reaching 1000 and often exceeding 3000 MJ·mm·(ha·h·year) –1 (Andreoli, 2018). Examples include studies in Malaysia with an R factor of 2375–2875 MJ·mm·(ha·h·year) –1 (Mahamud et al., 2021), in Anambra with 3894–4510 MJ·mm·(ha·h·year) –1 (Fagbohun et al., 2016), and in New Caledonia with 1030–2103 MJ·mm·(ha·h·year) –1 (Andreoli, 2018). Lower R factor values are usually a characteristic of semi‐arid regions (Ebabu et al., 2022; Xiong et al., 2019).…”
Section: State Of Rusle Modeling In Nigeriamentioning
confidence: 99%